2021
DOI: 10.1136/bmjsem-2020-000935
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effects of turmeric or curcumin extract on pain and function for individuals with knee osteoarthritis: a systematic review

Abstract: PurposeTo determine whether supplementation with turmeric or curcumin extract effects pain and physical function in individuals with knee osteoarthritis (OA). Second, we investigated the therapeutic response (pain and function) of turmeric compared with non-steroidal anti-inflammatory drugs (NSAIDs).MethodsA search was conducted in MEDLINE, Embase, CINAHL and Cochrane Review. Inclusion criteria included randomised controlled trials reporting pain and physical function in humans with knee OA comparing turmeric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 39 publications
0
28
0
8
Order By: Relevance
“…Curcumin has been extensively studied under experimental conditions as well as human clinical studies including treatment of osteoarthritis [23,[28][29][30][31], and bioavailability of curcuminoids plays an important role in the bioactivity such as exhibiting antioxidant and anti-inflammatory properties [32]. A recent study that used cell-based experimental models of osteoarthritis demonstrated that curcumin suppresses inflammation by blocking the NF-jB-Sox9 signaling pathway that plays a critical role in initiation of pathogenesis of osteoarthritis [29].…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin has been extensively studied under experimental conditions as well as human clinical studies including treatment of osteoarthritis [23,[28][29][30][31], and bioavailability of curcuminoids plays an important role in the bioactivity such as exhibiting antioxidant and anti-inflammatory properties [32]. A recent study that used cell-based experimental models of osteoarthritis demonstrated that curcumin suppresses inflammation by blocking the NF-jB-Sox9 signaling pathway that plays a critical role in initiation of pathogenesis of osteoarthritis [29].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies of oral curcumin showed promising results in alleviating OA symptoms [ 72 ]. Several studies have shown benefits on the pain and functional scores of OA after administering oral curcumin alone or as an adjunct [ 73 , 74 , 75 , 76 , 77 ].…”
Section: Anti-inflammatory Properties Of Curcuminmentioning
confidence: 99%
“…More recently, turmeric has been investigated for its anti-inflammatory properties due to its active ingredient, curcumin. Curcumin makes up 3% to 10% of the turmeric powder that can be extracted, 21 and the extract itself has been shown to have similar effect to NSAIDs through affecting the signaling of pro-inflammatory cytokines including interleukins, phospholipase A2, 5-lipoxygenase (5-LOX), and cyclooxygenase-2 (COX-2) by affecting nuclear factor kappa light-chain enhancer of activated B cells (NF-κB) activity. 22 In a study by Plummer et al 22 in 1999, it was shown, using NF-κB transfection assays, that curcumin decreases NF-κB transactivation.…”
Section: Turmericmentioning
confidence: 99%